Die Langfrist-Entwicklung des Automobilmarkts in Deutschland. - Dudenhöffer, Ferdinand (Deutscher Verkehrs-Verlag, 2004)
Die Entwicklung des deutschen Automarkts in den vergangenen 30 Jahren zeigte kontinuierlich "nach oben". Seit 1970 steigt der Fahrzeugbestand in Deutschland und wird Ende 2003 mit 45 Mio. Pkw einen neuen Höchststand erreichen. difu

Viewed from a long term perspective, significant changes are likely to happen in the private car market. It is anticipated that, up to 2030, car usage will increase continuously (one car per 1,000 residents) while the highest number of cars is estimated to reach beyond the 51 m level in Germany by 2025. The car market is expected to show a downward trend by 2015 due to the demographic evolution. Declining population figures and the ever ageing population are taken as the prime causes for the ongoing structural changes in Germany's car market. Lower car sales and the over-sixties' leading role as buyers are challenging factors for the car manufacturing industry that ought to shift its focus from the high level of car production to enhanced quality product growth. difu
Keywords: Individualverkehr; Straßenverkehr; Autoverkehr; Personenkraftwagen; Kraftfahrzeug; Bevölkerungsdichte; Kraftfahrzeugindustrie; Prognose; Verkehrsdichte; Fahrzeugdichte; Kraftfahrzeugmarkt